Distinguishing Late Holocene Storm Deposit From Shore-normal Beach Sediments From the Gulf of Thailand - Kongsen, Stapana; Phantuwongraj, Sumet; Choowong, Montri (Frontiers in Earth Science, 2021)
Grain size, as one of sedimentological proxies, coupled with a detailed description of the sedimentary structures and luminescence dating were used to unveil the sediment sources and transport process of the Holocene ancient coastal storm events recorded in the beach ridge plain, wet swale and muddy environments at Prachuap Khiri Khan, in the Southern Peninsula of Thailand. In this study, a total of 141 sand samples were collected from the shore-normal beach process and analyzed for layers of candidate storm deposits, revealing at least 21 candidate coastal storm events. The grain size distribution of beach sediments was, in general, unimodal, whilst the candidate storm sediments revealed a mixed combination of multimodal, bimodal and unimodal distributions. Plots of mean grain size against skewness and kurtosis and of skewness against kurtosis could differentiate storm deposits from shore-normal beach sediments. Sedimentary structures preserved in the ancient coastal storm deposits included parallel and inclined landward laminations, mud rip-up clasts, layers of shell fragments, a pebble grain, normal and reverse grading and sharp lower and upper contacts. Candidate storm layers overlain on a dry beach ridge intervened with mud in a swale showed a finer and thinner landward deposit. Marine shell fragments, smaller foraminifers, ostracod and scaphopod (tusk shell), were well preserved. Based on optically stimulated luminescence dating and a correlated accelerator mass spectrometry age, multiple layers of sand derived from different frequencies of coastal storms were deposited over the middle to late Holocene.